Pengaruh Audit Tenure, Opini Audit Tahun Sebelumnya, Debt Default daan Opini Shopping Terhadap Penerimaan Opini Audit Going Concern (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2017-2021) - Anugraha, Arda Laksmana; Nugroho, Wawan Sadtyo (Prosiding University Research Colloquium, 2022)
This study aims to examine the effect of audit tenure, previous year's audit opinion, debt default, and shopping opinion on the provision of going concern audit opinions. The population of this study was conducted in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sampling technique used in this study using purposive sampling method and obtained a sample of 36 companies. The data in this study is secondary data. Giving going concern audit opinion is measured by using a dummy variable. Hypothesis testing was performed using logistic regression analysis. The results of the study indicate that the previous year's audit opinion has a positive effect on the acceptance of going concern audit opinions. Meanwhile, audit tenure, debt default, and opinion shopping have no effect on the acceptance of going concern audit opinion.